Implementing Assistive and Autonomous Agents: A Technical Framework for Business Transformation with Google Cloud - Ashutosh Rana, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the implementation framework for assistive and autonomous agents utilizing Google Cloud's infrastructure, focusing on their transformative impact on business operations and decision-making processes. The article examines the distinct characteristics and applications of both agent types, highlighting how assistive agents enhance human capabilities through real-time analysis and decision support, while autonomous agents operate independently using sophisticated self-learning algorithms. The article delves into the technical infrastructure requirements, including data processing pipelines, security frameworks, and integration components essential for successful deployment. Through detailed analysis of implementation best practices, the article addresses critical aspects such as assessment methodology, change management strategies, and performance monitoring. It explores future trends in AI agent technology, industry-specific applications, and evolving human-AI collaboration paradigms. By providing a structured approach to implementing AI agents using Google Cloud services, this article offers organizations a comprehensive guide for achieving successful digital transformation while maintaining security, compliance, and operational efficiency.
Keywords: Artificial Intelligence Agents; Google Cloud Infrastructure; Business Transformation; Human-AI Collaboration; Implementation Framework